The Development of the New Tapestry: 25 Years of Experiment in Polish Tapestry. (2nd October 2018) - Jefferies, Janis
Abstract: A report written in 1976 for the British Council post awards for studying with Magdalena Abakanowicz at the Academy of Fine Arts in Poznan and a 3 month tour of other art schools and workshops in Poland. As an historical account and personal reflection, the report notes the pedagogical differences and practices between Warsaw, Krackow, Gdansk, Lodz and Poznan.